2017
DOI: 10.52166/kata.v4i1.1633
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Media Instagram Model Quantum Teaching Terhadap Kemampuan Menulis Puisi Siswa Kelas X SMK Hasyim Asy’ari Pucuk Lamongan

Abstract: Penelitian ini bertujuan untuk mengetahui: (1) pengaruh media Instagram model Quantum Teaching ditinjau dari aktivitas siswa, (2) pengaruh media Instagram model Quantum Teaching ditinjau dari aktivitas guru, (3) pengaruh media Instagram model Quantum Teaching ditinjau dari ketuntasan belajar, dan (4) pengaruh media Instagram model Quantum Teaching ditinjau dari respon siswa kelas X SMK Hasyim Asy’ari Pucuk Lamongan. Jenis penelitian ini adalah penelitian kuantitatif melalui hasil uji coba eksperimen. Populasi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Based on the results of the study it was found that the quantum teaching and CIRC methods had an effect on students' description writing skills. The results of research on quantum teaching have had a positive and significant effect on several previous studies on students' writing skills (Listiawati, Selirowangi, & Lestari, 2017;Setyarini & Mulyono, 2018). The results of this study are in line with several previous studies which showed that the CIRC method had a positive and significant effect on students' description writing skills (Anita, 2020;Sari, 2017;Suratiah & Suroso, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Based on the results of the study it was found that the quantum teaching and CIRC methods had an effect on students' description writing skills. The results of research on quantum teaching have had a positive and significant effect on several previous studies on students' writing skills (Listiawati, Selirowangi, & Lestari, 2017;Setyarini & Mulyono, 2018). The results of this study are in line with several previous studies which showed that the CIRC method had a positive and significant effect on students' description writing skills (Anita, 2020;Sari, 2017;Suratiah & Suroso, 2018).…”
Section: Discussionsupporting
confidence: 90%